THE SYNTHESIS OF TURATH AND MODERN INSTRUCTIONAL DESIGN: ENHANCING FIQH AL-MAWARITH MASTERY AT MAKTAB NUBDZAT AL-BAYAN - Ismail Ismail; Moh. Takwil; Akhmad Fauzi Sayuti; Ali Ridho; Ach. Sayyi; Ahmad Fauzi (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the instructional strategies used in teaching fiqh mawarits (Islamic inheritance law) at Maktab Nubdzat al-Bayan (Maktuba), a pesantren-based institution within the Syafi‘i tradition. The research employs a qualitative case study approach, collecting data through observations, analysis of primary teaching texts (Nadhm al-Rahbiyah and Khulashat al-Kalam), and documentation of assessment procedures. The findings reveal that Maktuba's curriculum is systematically structured based on classical texts, covering topics such as heir classification, computational methods, and exceptional cases. Pedagogically, Maktuba combines traditional pesantren methods (sorogan, bandongan, memorization, musyawarah, and i‘lan) with contemporary instructional theories like scaffolding, explicit instruction, and cognitive load management. Additionally, its evaluation system includes written and oral exams, memorization assessments, and performative i‘lan, measuring cognitive, procedural, and communicative competencies. This study highlights that the pedagogical model at Maktuba integrates classical Islamic scholarship with modern educational methods, demonstrating that pesantren-based teaching can maintain epistemic rigor while adapting to contemporary needs in Islamic legal education.